Proyecto de factibilidad para la implementación de una empresa de Spa (Centro de Hidroterapia) en el cantón Joya de los Sachas, de la provincia de Orellana, para el año 2016 - Ramírez Abad, María Gabriela (2017)
The objective of this research is to determine the feasibility of creating a SPA company (hydrotherapy center) in the canton of Joya de los Sachas, province of Orellana, which allowed the use of different methods and techniques that research allows to perform, such as the Deductive method, the Inductive Method, the Statistical Method and the Analytical Method, as well as the use of bibliographic materials, surveys and virtual material. The use of all these methods and techniques made it possible to reach the culmination of this work, since in order to achieve it, it was necessary to follow the steps of application, understanding and demonstration of it. In the market study conducted in the corner of Joya de los Sachas, with a sample of 371 people; tabulated the surveys have been analyzed and the results have been inferred to then perform the market analysis, determining the Potential Demand of 9,043 PEA, the Real Demand 8,862 PEA, Effective Demand of 110,544 SPA services. The offer of 34,100 services and the unsatisfied demand of 75,444 SPA services, which made it possible to determine that the project can and should be executed, based on the results obtained in the analysis of the demand, supply and levels of commercialization of this service. The installed capacity of the project determines that the company will be able to offer 6,240 SPA services and the capacity used will be 4,992 SPA services, of which 7.88% of the unmet demand will be used, and the location of the same will be determined which will be located in the city of Joya de los Sachas. The service process demands the use of adequate equipment, which will guarantee a quality service at moderate prices. The project's engineering is then developed by determining the process diagrams, the characteristics of operability and management, technical requirements such as equipment, facilities, furniture and equipment. Likewise, an administrative study was carried out determining as a Limited Liability Company, and with the functional organic structure at the hierarchical levels both Legislative, Executive, Advisory Level, Support Level Support, Operational Level, as well as the function manuals, organizational charts; that served as a guideline to implement a good organization, since it will have the following staff: Manager, a Contadora Secretary, a Guardian, who will be part of the Administrative staff, and the operating personnel distributed as follows: two workers and a salesman. The project reaches an investment of $ 40,777.40 and will be financed with a contribution from the partners of 50.95% of the total investment corresponding to $ 20,777.40 and a loan that will maintain the project with the Banco del Pichincha will constitute the 49.05% corresponding to 20,000.00 dollars at 5 years term at 15% annual interest. The financial evaluation presents the following results: according to the NPV of this project gives us a positive value of 34,219.86 dollars, which indicates that the project or investment is convenient. For the present project, the TIR is 31.65%, this value being satisfactory for the project, the time that would be required to recover the original investment would be 3 years, 3 months and 20 days, for the present project, the sensitivity values they are less than one, therefore the changes in costs and revenues increased 25.5% and decreased by 18.2%, respectively, that is, the project is not sensitive to these changes. In relation to the Environmental and Social evaluation, the company does not have any environmental impact.